ЭТНОГРАФИЧЕСКИЙ АНАЛИЗ ТРАДИЦИОННОГО ПРОИЗВОДСТВА ВОЙЛОЧНОГО ПОКРЫТИЯ ЮРТЫ (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article presents a detailed analysis of the traditional technology of felt production for yurt coverings. The stages of preparation for processing are considered, including shearing,мsorting and cleaning of sheep wool, as well as methods of its processing (washing, drying, combingмand loosening) for subsequent felting. Particular attention is paid to the structural design of the components of the felt covering of the yurt (tuurduk, uzyuk, tunduk zhabuu, eshik), their decorative processing and fastening elements.
Keywords: yurt, felt, sheep wool, ethnography, craft, regional features.